2010
DOI: 10.1038/leu.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the base excision repair pathway and graft-versus-host disease

Abstract: Graft-versus-host disease (GVHD) is a frequent complication after hematopoietic cell transplant (HCT). Tissue damage as a result of chemo-radiation injury is the initiating event in the pathogenesis of acute GVHD. Variations in DNA repair can influence the amount of tissue damage in response to alkylating agents and ionizing radiation used as conditioning during HCT. Since DNA damage caused by these agents is repaired by the Base Excision Repair (BER) pathway, we hypothesized that single nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…For example, two single-nucleotide polymorphisms in the heparanase gene associated with high recipient heparanase levels correlated with extensive cGvHD53 and polymorphisms in the PARP1 gene have been associated with a higher risk of cGvHD 54…”
Section: Recent Developmentsmentioning
confidence: 99%
“…For example, two single-nucleotide polymorphisms in the heparanase gene associated with high recipient heparanase levels correlated with extensive cGvHD53 and polymorphisms in the PARP1 gene have been associated with a higher risk of cGvHD 54…”
Section: Recent Developmentsmentioning
confidence: 99%
“…They have been evaluated for association with several diseases including GVHD. [7][8][9][10] Our group has previously shown a risk model using SNPs to predict patients with high risk of developing aGVHD and hence decreased OS. 11 Other studies have also examined SNPs to predict the onset of GVHD, but not their response to steroid therapy or development of SR aGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…The rela onship between carriership of certain allele variants of genes coding for products with roles in BER and the risk of development of various tumours was established around the same me [214]. Later, it was shown that some polymorphic variants of hOGG1 (the human homologue of Ogg1), MUTYH (the mammalian homologue of MutY, A/G-specific adenine DNA glycosylase) and G/T thymidine glycosylase (TDG)may modulate the transplant-related mortality in recipients of allogeneic haematopoie c stem cells [215,216]. It has been already proven, albeit in animal models only, that muta ons in some of the human genes, coding for AP-lyases are associated with mul factorial disease, such as metabolic syndrome [217].…”
Section: Base Excision Repairmentioning
confidence: 99%
“…The carriership of some polymorphic variants of PARP have been found to play a role in the cons tu on of the risk for development of chronic gra -versus-host dis¬ease a er transplanta on of allogeneic haematopoie c stem cells [215,216]. A polymorphism in a processed pseudogene of PARP1, located on chromosome 13 (13q33) was reported to be associated with increased risk for several common cancers [922].…”
Section: Brca1 and Brca2mentioning
confidence: 99%